Determination of serum isometamidium levels in sheep and goats under field conditions using isometamidium-ELISA - Wewsonga, J. O; Murilla, G. A.; Kibugi, J. K; Jones, T. W (My University, 2000)
Twenty eight sheep and 28 goats were treated with isometamidium chloride (Samorin®, hone Merieux, Lyon, France) at a dose of 1 mg/kg body weight (bw) by intramuscular injection. All the animals were grazed in a tsetse-infested area. They were monitored for anaemia, body weight, anti-trypanosome antibodies and serum isometamidium concentration using the isometamidium enzyme-linked immunosorbent assay (ELISA) for more than 80 days after treatment. Serum isometamidium levels were higher in goats than in sheep throughout the experimental period. Isometamidium was still detectable in sheep and goats for up to 77 and 98 days, respectively, alter treatment (detection limit=0.1 ng/ml). The isometamidium elimination half-lives in sheep and goats were approximately 13.8 and 17.4 days, respectively. No trypanosomes were detected in either the isometamidium-treated or untreated control animals. The present study demonstrated that the isometamidium-ELISA, originally developed for use in cattle, may be equally useful in monitoring the drug in sheep and goats. The elimination half-lives and serum isometamidium levels were markedly higher in goats than in sheep. This could have important implications for chemoprophylaxis in small ruminants under field conditions.